Mercury Analysis of Body Lotion Cosmetic Using CVAAS Method: Case Study of Distributed Product in Banda Aceh - Eka Safitri; Irmawati Irmawati; Khairi Suhud; Nurul Islami (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
The aim of this work is to determine the concentration of mercury in body lotion from several brands that are available in Banda Aceh. This research expected to provide information for the public and government related to the negative effects of harmful cosmetics that widely circulated. This information is useful into consideration of policy-making and monitoring the use of Hg metal. This study determined the type of body lotion cosmetics containing Hg metal by using Cold Vapor Atomic Absorption Spectroscopy (CVAAS) method. There are 22 samples and 11 of them have been selected by purposive sampling. The standard Hg calibration curve produces a linear line with the equation y = 0.0874x + 0.0729, and the correlation coefficient (R2) value of 0.9726. LOD value is 0.004854 ppb, and LOQ is 0.01681 ppb. The positive results were obtained from samples code TB3= 0.046, TB6= 0.01, and TB13= 0.004 ppb respectively. These results indicated the mercury level was still lower than 1 mg/L the threshold by drug and food control centers (BPOM).